Sleep Disruption in Epilepsy: Ictal and Interictal Epileptic Activity Matter - Peter-Derex, Laure; Klimes, Petr; Latreille, Véronique; Bouhadoun, Sarah; Dubeau, François; Frauscher, Birgit (Annals of neurology, 2020)
OBJECTIVE: Disturbed sleep is common in epilepsy. The direct influence of nocturnal epileptic activity on sleep fragmentation remains poorly understood. Stereo-electroencephalography paired with polysomnography is the ideal tool to study this relationship. We investigated whether sleep-related epileptic activity is associated with sleep disruption. METHODS: We visually marked sleep stages, arousals, seizures, and epileptic bursts in 36 patients with focal drug-resistant epilepsy who underwent combined stereo-electroencephalography/polysomnography during presurgical evaluation. Epileptic spikes were detected automatically. Spike and burst indices (n/sec/channel) were computed across four 3-second time windows (baseline sleep, pre-arousal, arousal, and post-arousal). Sleep stage and anatomic localization were tested as modulating factors. We assessed the intra-arousal dynamics of spikes and their relationship with the slow wave component of non-rapid eye-movement sleep (NR) arousals. RESULTS: The vast majority of sleep-related seizures (82.4%; 76.5% asymptomatic) were followed by awakenings or arousals. The epileptic burst index increased significantly before arousals as compared to baseline and postarousal, irrespective of sleep stage or brain area. A similar pre-arousal increase was observed for the spike index in NR stage 2 and rapid eye-movement sleep. In addition, the spike index increased during the arousal itself in neocortical channels, and was strongly correlated with the slow wave component of NR arousals (r = 0.99, p < 0.0001). INTERPRETATION: Sleep fragmentation in focal drug-resistant epilepsy is associated with ictal and interictal epileptic activity. The increase in interictal epileptic activity before arousals suggests its participation in sleep disruption. An additional increase in the spike rate during arousals may result from a sleep-wake boundary instability, suggesting a bidirectional relationship. ANN NEUROL 2020;88:907-920.
Keywords: Young Adult; záchvaty; Sleep Deprivation; Electroencephalography; Male; spánková deprivace; mladý dospělý; Arousal; Sleep Wake Disorders; elektroencefalografie; Adult; dospělí; mužské pohlaví; polysomnografie; Seizures; epilepsie; spánek pomalých vln; lidé; ženské pohlaví; Drug Resistant Epilepsy; Humans; Sleep Stages; refrakterní epilepsie; poruchy spánku a bdění; arousal; Sleep, Slow-Wave; Epilepsy; Female; lidé středního věku; stadia spánku; Polysomnography; Middle Aged